Impact of restrictive physiology on intrinsic diastolic right ventricular function and lusitropy in children and adolescents after repair of tetralogy of Fallot. Issue 22 (3rd October 2010) - Apitz, Christian; Latus, Heiner; Binder, Wolfhard; Uebing, Anselm; Seeger, Achim; Bretschneider, Christiane; Sieverding, Ludger; Hofbeck, Michael
Abstract : Background: Restrictive right ventricular (RV) physiology is a phenomenon considered potentially beneficial when detected in children and adolescents with repaired tetralogy of Fallot (ToF). It is typically characterised by antegrade flow in the pulmonary artery in late diastole at the time of atrial contraction. However, little is known about the impact of restrictive physiology on intrinsic diastolic RV function or lusitropy. Methods: Diastolic function was prospectively assessed at baseline level and during dobutamine infusion using the pressure–volume conductance system. End diastolic forward flow in the pulmonary artery was measured by MRI. Results: Twenty-five patients aged 17.9±7.5 years were studied. Although the end diastolic RV pressure, the time constant of isovolumic RV relaxation (τ) and dP/dtmin were similar between both groups, the slope of the end diastolic pressure–volume relationship (Eed) was significantly higher in the restrictive group indicating increased diastolic stiffness in these patients (0.14±0.05 vs 0.06±0.01, p=0.03). Dobutamine stress, however, led to an increase in Eed in the entire ToF cohort indicating an abnormal diastolic response to catecholamines in these patients. Conclusions: Diastolic RV stiffness of repaired ToF patients with restrictive physiology is increased. The lusitropic response of the RV to β adrenergic agents is abnormal after ToF repair regardless of whether restrictive physiology is present or not. This has potential implications, particularly for postoperative drug management.